Liber amicorum-speculum siderum : nūt astrophoros : papers presented to Alicia Maravelia - Maniati, Antigoni (Archaeopress Egyptology, 2016)
In this volume, a pleiade of Egyptologists, Archaeologists, Archaeoastronomers, Archaeoanthropologists, Historians and other scholars from fifteen countries have combined their efforts in order to honour Alicia Maravelia